The role of TAM receptors in bone - Engelmann, Janik; Ragipoglu, Deniz; Ben-Batalla, Isabel; Loges, Sonja (International journal of molecular sciences, 2024)
The TAM (TYRO3, MERTK, and AXL) family of receptor tyrosine kinases are pleiotropic regulators of adult tissue homeostasis maintaining organ integrity and self-renewal. Disruption of their homeostatic balance fosters pathological conditions like autoinflammatory or degenerative diseases including rheumatoid arthritis, lupus erythematodes, or liver fibrosis. Moreover, TAM receptors exhibit prominent cell-transforming properties, promoting tumor progression, metastasis, and therapy resistance in various cancer entities. Emerging evidence shows that TAM receptors are involved in bone homeostasis by regulating osteoblastic bone formation and osteoclastic bone resorption. Therefore, TAM receptors emerge as new key players of the regulatory cytokine network of osteoblasts and osteoclasts and represent accessible targets for pharmacologic therapy for a broad set of different bone diseases, including primary and metastatic bone tumors, rheumatoid arthritis, or osteoporosis.